Strength and chloride penetration performance of concrete using coal bottom ash as coarse and fine aggregate replacement - Zaimi, M. N. S.; Nur Farhayu, Ariffin; Sharifah Maszura, Syed Mohsin; Nor Hasanah, Abdul Shukor Lim; Fadzil, Mat Yahaya; Khairunisa, Muthusamy; Saffuan, Wan Ahmad (IOP Science, 2021)
Since 1987, Malaysia had used coal as a product to generate electricity. One of the main or the largest power plant in Malaysia is Tanjung Bin power plant at kukup, Johor. As a coal-based power plant, tonnes of coal bottom ash had been burned every day and the waste is wasted without specific economic benefit. Other than that, the waste generated are dangerous as it involved in environmental risk such as landfill ash reservoir. Therefore, this paper presents one of the alternative ways to manage the coal waste by cooperative it into concrete. This research study focuses on strength and durability performance of the concrete containing coal bottom ash as a coarse and fine aggregates replacement. The tests conducted was workability on fresh concrete, compressive strength test and chloride penetration test in 5% sodium chloride. The results show that the concrete containing coal bottom ash has low workability compare with normal concrete without coal bottom ash. Compressive strength test with coal bottom ash resulted higher than normal concrete. In chloride solution, the concrete containing coal bottom ash replacement shows better performance compare to normal concrete. Thus, it can be concluded that by using coal bottom ash in concrete as fine and coarse aggregates replacement, the performance in term of strength and chloride resistance are better compare to normal concrete. On the other hand, by using it in concrete, the waste generated dump in landfill can be reduced.